Describing of Ethnopedagogical Leadership Contribution to Towani Tolotang Community Based on Local Wisdom Values in Elementary Schools - Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The research objective is to know the dialectic of ethnopedagogical leadership on the trust of the Towani Tolotang community. The research method uses descriptive research. The data were collected using a questionnaire from a variable in the form of a discourse on the local wisdom of the Towani Tolotang community which is manifested in the concept of "Perrinyameng". There is a correlation between humans and God which contains the value of obedience to the Gods of Seuwae as well as respect for Wa 'as a traditional leader. The meaning of Perrinyameng is a willingness to learn and work hard, high respect for fellow human beings, and high social sensitivity towards the fate of fellow humans. The main driving pillars of the Towani Tolotang community are in the form of preservation and development of local wisdom culture as well as disseminating government policies and programs. The results showed that Wa 'leadership as social control in government, role models, motivators, traditional leaders, preserving Bugis culture, especially the Towani Amparita community, disseminating good governance policies and programs as well as the main driving pillar for the preservation and development of local wisdom culture in government in the Kelurahan Amparita, Tellu LimpoE District, Sidenreng Regency